Annotated keys to the species of Megaspilidae (Hymenoptera: Ceraphronoidea) of the Neotropical Region - Pezzini, Cleder; Köhler, Andreas (EntomoBrasilis, 2017)
Abstract. A key to the species of Megaspilidae occurring in Neotropical Region is given, and information on the 20 species in four genera is provided, including data on their distribution and host associations. The Megaspilidae fauna is still poorly known in the Neotropical region and more studies are necessary. Chaves de identificação para as espécies de Megaspilidae (Hymenoptera: Ceraphronoidea) na Região Neotropical Resumo. É fornecida chave de identificação para os quatro gêneros e 20 espécies de Megaspilidae que ocorrem na Região Neotropical assim como dados sobre as suas distribuições e associações. A fauna de Megaspilidae da Região Neotropical é pouco conhecida e mais estudos são necessários.